(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Low levels of community participation in routine religious activities remain a significant challenge in strengthening religious awareness in rural areas. Mosques, as central institutions in Muslim communities, have strategic potential to promote community empowerment through structured Islamic programs. However, the effectiveness of such programs in enhancing religious awareness, particularly in village contexts, still requires empirical investigation. This study examines the effectiveness of Islamic-based community empowerment programs in enhancing religious awareness in Nagari Silago, Dharmasraya Regency. A quantitative survey method was employed using questionnaires distributed to 50 respondents selected through simple random sampling. The findings reveal that the level of religious awareness is moderate, with a mean score of 3.2 on a 5-point Likert scale. While the implemented Islamic programs improved community interest and religious understanding, they did not significantly influence consistent religious behavior. These results indicate that sustainable, participatory, and context-based programs are necessary to foster deeper and long-term religious awareness. This study contributes to the development of community empowerment strategies in rural religious contexts.